Preparation method and application of cubic phase TiC nanosheet

By intercalation thinning, C-coated and high-temperature calcining on multi-layer Ti3C2Tx, cubic phase TiC nanosheets were prepared, which solved the problem that titanium carbide nanosheets were easily oxidized in high-temperature environments, and achieved excellent electromagnetic wave absorption performance in room temperature and high-temperature environments.

CN119569058APending Publication Date: 2025-03-07SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411738094.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing titanium carbide nanosheets are easily oxidized in high temperature environments, resulting in reduced conductivity and electromagnetic wave absorption performance, and cannot be effectively applied in room temperature and high temperature environments.

Method used

By intercalating the multi-layer Ti3C2Tx, a small layer of Ti3C2Tx was obtained, and then C-coated with 3-aminophene was used to increase the C content of the Ti3C2Tx surface, and finally calcined at high temperature under an argon atmosphere to obtain a cubic phase TiC nanosheet.

Benefits of technology

The prepared cubic phase TiC nanosheets have a large specific surface area and aspect ratio, and the electromagnetic wave absorption performance is best when the load is 40%, and are suitable for electromagnetic wave absorption applications in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569058A_ABST
    Figure CN119569058A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic nonmetallic materials, and particularly relates to a preparation method and application of a cubic phase TiC nanosheet. The preparation method comprises the following steps: firstly, taking multi-layer Mxene (Ti3C2Tx) as a raw material, taking tetramethylammonium hydroxide as an intercalation agent, and thinning intercalation to obtain less-layer Ti3C2Tx; then 3-aminophenol is used for carrying out coating treatment on the Ti3C2Tx nanosheets, and the content of C on the surfaces of the few-layer Ti3C2Tx nanosheets is increased; and finally, taking the coated few-layer Ti3C2Tx as a template, and carrying out high-temperature calcination treatment in an argon atmosphere to obtain the cubic-phase TiC nanosheet. The cubic phase titanium carbide nanosheet prepared by the method has the advantages of controllable sheet shape, simple operation and mass production, and can be used in the field of electromagnetic wave absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic materials, and specifically relates to a preparation method and application of cubic phase TiC nanosheets. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] At present, most titanium carbide nanosheets are Mxene (Ti3C2T x ) material, with excellent water solubility, electrochemical activity, high conductivity, electromagnetic wave absorption and shielding performance, has attracted widespread attention from researchers. However, its thermal stability is very poor and needs to be used in low temperature environments. When it is above 100°C, it is easily oxidized to TiO2, thus losing its excellent conductivity and electromagnetic wave absorption ability; and it cannot be exposed to air for a long time at room temperature. This makes Mxene phase titanium carbide nanosheets (Ti3C2T x ) cannot be applied to fields such as wave absorption at room temperature and high temperature environments.

[0004] Therefore, improving the oxidation resistance and high-temperature stability of titanium carbide nanosheets while retaining their excellent electrical conductivity is the focus and difficulty of research in this field. Studies have reported that cubic titanium carbide (TiC) is a very potential absorber in the field of high-temperature wave absorption because of its excellent electrical conductivity, oxidation resistance and high-temperature stability; and the nanosheet morphology has a larger specific surface area and a larger aspect ratio, so it has better performance than granular materials. However, the titanium carbide prepared by the existing method for preparing titanium carbide powder is generally granular and cannot better meet the needs of applications in the fields of electromagnetic wave absorption and so on. Therefore, those skilled in the art are in urgent need of developing a method for efficiently preparing cubic phase TiC nanosheets. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a method for preparing cubic TiC nanosheets and their application. x As raw materials, it was thinned by intercalation with tetramethylammonium hydroxide solution to obtain a few-layer Ti3C2T x ; Then the obtained few-layer Ti3C2T x Using 3-aminophenol (3-AP) for C coating to improve Ti3C2T x The C content on the surface; finally, the carbon-coated Ti3C2T xBy high-temperature calcination treatment in an argon atmosphere, cubic TiC nanosheets were obtained, and their electromagnetic wave absorption performance was tested. Thanks to the large specific surface area and aspect ratio of the nanosheet morphology, the electromagnetic wave absorption performance was optimal when the loading amount of the TiC nanosheets was 40%, and it has good application prospects.

[0006] Specifically, the present invention provides the following technical solutions:

[0007] In a first aspect of the present invention, a method for preparing cubic TiC nanosheets is provided, which comprises the following steps: adding Ti3C2T3C4O ... x , ammonia and formaldehyde, and condensation reaction was carried out to obtain carbon-coated Ti3C2T x , the carbon-coated Ti3C2T x The cubic TiC nanosheets are obtained by calcining.

[0008] Preferably, the Ti3C2T x is achieved by adding multilayer Ti3C2T x The mixed solution is added to the raw material powder to obtain a few-layer Ti3C2T x ;

[0009] The mixed solution includes 25% tetramethylammonium hydroxide solution and water; the volume ratio of the 25% tetramethylammonium hydroxide solution to water is 4:1.

[0010] Preferably, the multilayer Ti3C2T x The mass volume ratio of powder to mixed solution is 0.1-0.4 g:50 mL.

[0011] Preferably, the intercalation thinning process is to intercalate multiple layers of Ti3C2T x The solution obtained by mixing the powder and the mixed solution is first subjected to ultrasonic treatment for 0.5 to 2 hours, and then subjected to magnetic stirring operation; further preferably, the speed of the magnetic stirring is 1000 to 1200 r / min, and the stirring time is 24 to 48 hours.

[0012] Preferably, after the intercalation thinning process is completed, the intermediate needs to be filtered and washed with deionized water and ethanol in sequence, and then dried for 20 to 30 minutes to obtain a few-layer Ti3C2T x .

[0013] Preferably, the mass volume ratio of 3-aminophenol to deionized water in the aqueous solution of 3-aminophenol is 0.1-0.3 g:30 mL.

[0014] Preferably, the aqueous solution of 3-aminophenol and the Ti3C2Tx , the volume ratio of ammonia water and formaldehyde is 300:300:1~5:1~3.

[0015] Preferably, the solution after the condensation reaction needs to be centrifuged and dried in sequence;

[0016] Wherein, the centrifugal speed is 4600-4800 r / min, and the single centrifugal time is 7-10 min;

[0017] The centrifugation is firstly performed by centrifugation washing with deionized water for 2 to 3 times, and then by centrifugation washing with anhydrous ethanol for 1 to 2 times; the powder after the centrifugation is placed in an oven for drying at a drying temperature of 60° C. for a drying time of 2 to 4 hours.

[0018] Preferably, the calcination reaction is carried out in an inert atmosphere, and the inert atmosphere is one or a combination of hydrogen, nitrogen, and argon;

[0019] Wherein, the flow rate of the inert atmosphere is 80-120 sccm; more preferably, the flow rate of the inert atmosphere is 100 sccm.

[0020] Preferably, the calcination reaction is carried out by heating to 1200-1400° C. at a heating rate of 1-5° C. / min and keeping the temperature for 1-4 hours.

[0021] The second aspect of the present invention provides a cubic TiC nanosheet, which is prepared by the preparation method described in the first aspect.

[0022] The third aspect of the present invention provides an application of the cubic TiC nanosheets prepared by the preparation method described in the first aspect and / or the cubic TiC nanosheets described in the second aspect in the field of electromagnetic wave absorption.

[0023] The fourth aspect of the present invention provides a method for testing the electromagnetic wave absorption performance of cubic TiC nanosheets: the cubic TiC nanosheets prepared in the first aspect of the present invention are uniformly mixed with paraffin, and the electromagnetic wave absorption performance of the cubic TiC nanosheets is tested after post-treatment of the mixture.

[0024] Preferably, the uniform mixing of the cubic TiC nanosheets and paraffin wax refers to weighing TiC nanosheets and paraffin wax according to a certain loading amount of TiC nanosheets, melting the paraffin wax through heating treatment, and then stirring, thereby achieving uniform mixing of the TiC nanosheets in the paraffin wax.

[0025] Preferably, the loading amount of the TiC nanosheets is 20% to 60%; and the total mass of the TiC nanosheets and paraffin is controlled to be 0.1 g to 0.2 g.

[0026] More preferably, the loading amount of the TiC nanosheets is 35%, 40%, or 45%.

[0027] Preferably, the temperature of the heating treatment is 70-90°C.

[0028] Preferably, the post-treatment refers to cooling and granulating the paraffin wax and TiC nanosheet mixture after the heating treatment to obtain a paraffin wax and TiC nanosheet mixed powder, adding the mixed powder into a specific annular mold, and dry pressing to obtain an annular test sample.

[0029] More preferably, the dry pressing pressure is 1-10 MPa, and the holding time is 30-120 s.

[0030] Further preferably, the test sample is to use a vector network analyzer (E5071C) to perform electromagnetic parameter testing on the prepared annular sample, the test environment is at normal temperature and pressure, and the obtained electromagnetic parameters are converted through a formula to obtain the electromagnetic wave absorption performance of the test sample in the 2 to 18 GHz band.

[0031] One or more embodiments of the present invention have at least the following beneficial effects:

[0032] (1) The cubic TiC nanosheets prepared by the present invention are relatively thin, with a lateral size of micrometers, and have the advantage of being mass-producible. The examples show that the titanium carbide nanosheets have a uniform morphology, which is mainly due to the fact that the few-layer Ti3C2T x It acts as a template in the preparation of cubic titanium carbide nanosheets.

[0033] (2) The cubic phase TiC nanosheets prepared by the present invention have good electromagnetic wave absorption performance at different matching thicknesses from 4 to 18 GHz, and the loading amount of the TiC nanosheets is low, which is due to the large specific surface area and aspect ratio of the nanosheet morphology. When the loading amount of the TiC nanosheets is 40%, the electromagnetic wave absorption performance is the best. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0035] FIG1( a ) is a scanning electron microscope photograph of the cubic titanium carbide nanosheets prepared in Example 1 of the present invention, with a magnification of 5000 times;

[0036] FIG1( b ) is a scanning electron microscope photograph of the cubic titanium carbide nanosheets prepared in Example 2 of the present invention, with a magnification of 2500 times;

[0037] FIG1( c ) is a scanning electron microscope photograph of the cubic titanium carbide nanosheets prepared in Example 3 of the present invention, with a magnification of 10,000 times;

[0038] Figure 2 The few-layer Ti3C2T coated with different amounts of 3-aminophenol prepared in Examples 1 to 3 of the present invention x XRD pattern of

[0039] Figure 3 The few-layer Ti3C2T3 coated with different amounts of 3-aminophenol in Examples 1 to 3 of the present invention x XRD pattern of cubic phase titanium carbide nanosheets prepared after calcination;

[0040] Figure 4 The present invention is comparative example 1, example 2 and example 4 for the coated few-layer Ti3C2T x XRD patterns of cubic titanium carbide nanosheets prepared after calcination at different temperatures;

[0041] Figure 5 This is an image of the electromagnetic wave absorption performance of the TiC nanosheets at 2 to 18 GHz when the TiC nanosheet loading is 35% in Application Example 1 of the present invention;

[0042] Figure 6 This is an image of the electromagnetic wave absorption performance of the TiC nanosheets at 2 to 18 GHz when the TiC nanosheet loading is 40% in Application Example 2 of the present invention;

[0043] Figure 7 This is an image of the electromagnetic wave absorption performance of TiC nanosheets at 2 to 18 GHz when the TiC nanosheet loading is 45% in Application Example 3 of the present invention. DETAILED DESCRIPTION

[0044] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0045] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0046] Example 1 :This embodiment provides a method for preparing cubic phase TiC nanosheets

[0047] (1) Weigh 0.2 g of multilayer Ti3C2T xMxene was added to a 100 mL beaker, and 40 mL of deionized water and 10 mL of 25% tetramethylammonium hydroxide aqueous solution were added, respectively, and ultrasonicated for 30 min to make the multilayer Ti3C2T x Mxene is thoroughly mixed with the mixed solution.

[0048] (2) The mixed solution was magnetically stirred at a speed of 1000 r / min, the temperature was controlled at room temperature, and the stirring time was 24 h.

[0049] (3) The mixed solution after stirring and intercalation is filtered and washed to collect the intercalated few-layer Ti3C2T x , the powder was washed with deionized water and ethanol during the filtration process.

[0050] (4) The collected few-layer Ti3C2T x Add to 30 mL of deionized water and stir at 600 r / min for 30 min to make the few-layer Ti3C2T x Fully soluble in deionized water.

[0051] (5) Add 0.1 g of 3-aminophenol into 30 mL of deionized water and stir at 600 r / min for 30 min to completely dissolve the 3-aminophenol.

[0052] (6) 30 mL of few-layer Ti3C2T x The aqueous solution was poured into 30 mL of 3-aminophenol solution and stirred at 600 r / min for 5 min to ensure that the two solutions were fully mixed.

[0053] (7) Add 200uL of ammonia water to the mixed solution and stir at 600r / min for 30min.

[0054] (8) Add 200 μL of formaldehyde solution to the stirred mixed solution and stir for 30 min to allow 3-aminophenol and formaldehyde to react on the Ti3C2T x The condensation reaction is completed on the surface to achieve the few-layer Ti3C2T x The covering.

[0055] (9) The solution after the reaction was centrifuged and washed at a speed of 4600 r / min and a single centrifugation time of 10 min. During the centrifugation process, deionized water was used for centrifugation washing twice, and then anhydrous ethanol was used for centrifugation washing once. After drying at 60 ° C for 2 h, a coated Ti3C2T x .

[0056] (10) Finally, the coated few-layer Ti3C2T xThe calcination was carried out in a tube furnace at a high temperature of 1400°C, a heating rate of 5°C / min, and a holding time of 2h. The argon atmosphere was used for protection, and the argon flow rate was 100sccm. During the calcination process, the coated Ti3C2T x It is placed in a graphite crucible, and after calcination, cubic titanium carbide nanosheets are obtained.

[0057] Example 2 :This embodiment provides a method for preparing cubic phase TiC nanosheets

[0058] (1) Weigh 0.2 g of multilayer Ti3C2T x Mxene was added to a 100 mL beaker, and 40 mL of deionized water and 10 mL of 25% tetramethylammonium hydroxide aqueous solution were added, respectively, and ultrasonicated for 30 min to make the multilayer Ti3C2T x Mxene is thoroughly mixed with the mixed solution.

[0059] (2) The mixed solution was magnetically stirred at a speed of 1000 r / min, the temperature was controlled at room temperature, and the stirring time was 24 h.

[0060] (3) The mixed solution after stirring and intercalation is filtered and washed to collect the intercalated few-layer Ti3C2T x , the powder was washed with deionized water and ethanol during the filtration process.

[0061] (4) The collected few-layer Ti3C2T x Add to 30 mL of deionized water and stir at 600 r / min for 30 min to make the few-layer Ti3C2T x Fully soluble in deionized water.

[0062] (5) Add 0.2 g of 3-aminophenol into 30 mL of deionized water and stir at 600 rpm for 30 min to completely dissolve the 3-aminophenol.

[0063] (6) 30 mL of few-layer Ti3C2T x The aqueous solution was poured into 30 mL of 3-aminophenol solution and stirred at 600 r / min for 5 min to ensure that the two solutions were fully mixed.

[0064] (7) Add 200uL of ammonia water to the mixed solution and stir at 600r / min for 30min.

[0065] (8) Add 200 μL of formaldehyde solution to the stirred mixed solution and stir for 30 min to allow 3-aminophenol and formaldehyde to react on the Ti3C2T x The condensation reaction is completed on the surface to achieve the few-layer Ti3C2T x The covering.

[0066] (9) The solution after the reaction was centrifuged and washed at a speed of 4600 r / min and a single centrifugation time of 10 min. During the centrifugation process, deionized water was used for centrifugation washing twice, and then anhydrous ethanol was used for centrifugation washing once. After drying at 60 ° C for 2 h, a coated Ti3C2T x .

[0067] (10) Finally, the coated few-layer Ti3C2T x The calcination was carried out in a tube furnace at a high temperature of 1400°C, a heating rate of 5°C / min, and a holding time of 2h. The argon atmosphere was used for protection, and the argon flow rate was 100sccm. During the calcination process, the coated Ti3C2T x It is placed in a graphite crucible, and after calcination, cubic titanium carbide nanosheets are obtained.

[0068] Example 3 :This embodiment provides a method for preparing cubic phase TiC nanosheets

[0069] (1) Weigh 0.2 g of multilayer Ti3C2T x Mxene was added to a 100 mL beaker, and 40 mL of deionized water and 10 mL of 25% tetramethylammonium hydroxide aqueous solution were added, respectively, and ultrasonicated for 30 min to make the multilayer Ti3C2T x Mxene is thoroughly mixed with the mixed solution.

[0070] (2) The mixed solution was magnetically stirred at a speed of 1000 r / min, the temperature was controlled at room temperature, and the stirring time was 24 h.

[0071] (3) The mixed solution after stirring and intercalation is filtered and washed to collect the intercalated few-layer Ti3C2T x , the powder was washed with deionized water and ethanol during the filtration process.

[0072] (4) The collected few-layer Ti3C2T x Add to 30 mL of deionized water and stir at 600 r / min for 30 min to make the few-layer Ti3C2T x Fully soluble in deionized water.

[0073] (5) Add 0.3 g of 3-aminophenol into 30 mL of deionized water and stir at 600 rpm for 30 min to completely dissolve the 3-aminophenol.

[0074] (6) 30 mL of few-layer Ti3C2T xThe aqueous solution was poured into 30 mL of 3-aminophenol solution and stirred at 600 r / min for 5 min to ensure that the two solutions were fully mixed.

[0075] (7) Add 200uL of ammonia water to the mixed solution and stir at 600r / min for 30min.

[0076] (8) Add 200 μL of formaldehyde solution to the stirred mixed solution and stir for 30 min to allow 3-aminophenol and formaldehyde to react on the Ti3C2T x The condensation reaction is completed on the surface to achieve the few-layer Ti3C2T x The covering.

[0077] (9) The reaction solution was centrifuged and washed at a speed of 4600 r / min and a single centrifugation time of 10 min. During the centrifugation process, deionized water was used for centrifugation washing twice, and then anhydrous ethanol was used for centrifugation washing once. After drying at 60 ° C for 2 h, a carbon-coated few-layer Ti3C2T x .

[0078] (10) Finally, the coated few-layer Ti3C2T x The calcination was carried out in a tube furnace at a high temperature of 1400°C, a heating rate of 5°C / min, and a holding time of 2h. The argon atmosphere was used for protection, and the argon flow rate was 100sccm. During the calcination process, the coated Ti3C2T x It is placed in a graphite crucible, and after calcination, cubic titanium carbide nanosheets are obtained.

[0079] Example 4 :This embodiment provides a method for preparing cubic phase TiC nanosheets

[0080] (1) Weigh 0.2 g of multilayer Ti3C2T x Mxene was added to a 100 mL beaker, and 40 mL of deionized water and 10 mL of 25% tetramethylammonium hydroxide aqueous solution were added respectively. The multilayer Ti3C2T x Mxene is thoroughly mixed with the mixed solution.

[0081] (2) The mixed solution was magnetically stirred at a speed of 1000 r / min, the temperature was controlled at room temperature, and the stirring time was 24 h.

[0082] (3) The mixed solution after stirring and intercalation is filtered and washed to collect the intercalated few-layer Ti3C2T x , the powder was washed with deionized water and ethanol during the filtration process.

[0083] (4) The collected few-layer Ti3C2T xAdd to 30 mL of deionized water and stir at 600 r / min for 30 min to make the few-layer Ti3C2T x Fully soluble in deionized water.

[0084] (5) Add 0.2 g of 3-aminophenol into 30 mL of deionized water and stir at 600 rpm for 30 min to completely dissolve the 3-aminophenol.

[0085] (6) 30 mL of few-layer Ti3C2T x The aqueous solution was poured into 30 mL of 3-aminophenol solution and stirred at 600 r / min for 5 min to ensure that the two solutions were fully mixed.

[0086] (7) Add 200uL of ammonia water to the mixed solution and stir at 600r / min for 30min.

[0087] (8) Add 200 μL of formaldehyde solution to the stirred mixed solution and stir for 30 min to allow 3-aminophenol and formaldehyde to react on the Ti3C2T x The condensation reaction is completed on the surface to achieve the few-layer Ti3C2T x The covering.

[0088] (9) The solution after the reaction was centrifuged and washed at a speed of 4600 r / min and a single centrifugation time of 10 min. During the centrifugation process, deionized water was used for centrifugation washing twice, and then anhydrous ethanol was used for centrifugation washing once. After drying at 60 ° C for 2 h, a coated Ti3C2T x .

[0089] (10) Finally, the coated few-layer Ti3C2T x The calcination was carried out in a tube furnace at a high temperature of 1200°C, a heating rate of 5°C / min, and a holding time of 2h. The argon atmosphere was used for protection, and the argon flow rate was 100sccm. During the calcination process, the coated Ti3C2T x It is placed in a graphite crucible, and after calcination, cubic titanium carbide nanosheets are obtained.

[0090] Comparative Example 1 :This comparative example provides a method for preparing cubic phase TiC nanosheets

[0091] (1) Weigh 0.2 g of multilayer Ti3C2T x Mxene was added to a 100 mL beaker, and 40 mL of deionized water and 10 mL of 25% tetramethylammonium hydroxide aqueous solution were added, respectively, and ultrasonicated for 30 min to make the multilayer Ti3C2T x Mxene is fully mixed with the mixed solution;

[0092] (2) The mixed solution was magnetically stirred at a speed of 1000 r / min, the temperature was controlled at room temperature, and the stirring time was 24 h.

[0093] (3) The mixed solution after stirring and intercalation is filtered and washed to collect the intercalated few-layer Ti3C2T x , the powder was washed with deionized water and ethanol during the filtration process.

[0094] (4) The collected few-layer Ti3C2T x Add to 30 mL of deionized water and stir at 600 r / min for 30 min to make the few-layer Ti3C2T x Fully soluble in deionized water.

[0095] (5) Add 0.2 g of 3-aminophenol into 30 mL of deionized water and stir at 600 rpm for 30 min to completely dissolve the 3-aminophenol.

[0096] (6) 30 mL of few-layer Ti3C2T x The aqueous solution was poured into 30 mL of 3-aminophenol solution and stirred at 600 r / min for 5 min to ensure that the two solutions were fully mixed.

[0097] (7) Add 200uL of ammonia water to the mixed solution and stir at 600r / min for 30min.

[0098] (8) Add 200 μL of formaldehyde solution to the stirred mixed solution and stir for 30 min to allow 3-aminophenol and formaldehyde to react on the Ti3C2T x The condensation reaction is completed on the surface to achieve the few-layer Ti3C2T x The covering.

[0099] (9) The solution after the reaction was centrifuged and washed at a speed of 4600 r / min and a single centrifugation time of 10 min. During the centrifugation process, deionized water was used for centrifugation washing twice, and then anhydrous ethanol was used for centrifugation washing once. After drying at 60 ° C for 2 h, a coated Ti3C2T x .

[0100] (10) Finally, the coated few-layer Ti3C2T x The calcination was carried out in a tube furnace at a high temperature of 1000°C, a heating rate of 5°C / min, and a holding time of 2h. The argon atmosphere was used for protection, and the argon flow rate was 100sccm. During the calcination process, the coated Ti3C2T x It is placed in a graphite crucible and calcined.

[0101] Example 5: This example characterizes and tests the cubic titanium carbide nanosheets prepared in Examples 1 to 4 and Comparative Example 1.

[0102] from Figure 1(a) to Figure 1(c) It can be seen from the scanning images that the cubic titanium carbide nanosheets prepared in Examples 1 to 3 are all nanosheet-like in morphology, thin in thickness, and with a lateral size of 1 to 10 μm.

[0103] from Figure 2 It can be seen from the XRD patterns of Examples 1 to 3 that the few-layer Ti3C2T x , and did not change the few-layer Ti3C2T x The physical aspect;

[0104] from Figure 3 It can be seen from the XRD patterns that after high temperature calcination, the titanium carbide nanosheets prepared in Examples 1 to 3 have a x A phase transition occurred from the Mxene phase to the cubic phase, so the obtained titanium carbide nanosheets all had a cubic phase structure.

[0105] from Figure 4 It can be seen from the XRD spectrum of the coated few-layer Ti3C2T x After calcination at different temperatures, different phases are obtained. x After calcination at 1000°C, there are still impurity peaks of TiO2, and single cubic phase TiC nanosheets cannot be obtained; in Example 2 and Example 4, single cubic phase TiC nanosheets are obtained after calcination at 1400°C and 1200°C, respectively. However, compared with Example 4, the cubic phase TiC nanosheets obtained in Example 2 after calcination at 1400°C have sharper XRD diffraction peaks and better crystallinity. Application Example 1 :This application example tests the electromagnetic wave absorption performance of the titanium carbide nanosheets prepared in Example 2

[0106] (1) TiC nanosheets and paraffin were weighed according to a TiC nanosheet loading of 35%. The mass of the TiC nanosheets was 0.0533 g, and the mass of the paraffin was 0.08 g. They were added into a 5 mL beaker respectively.

[0107] (2) The small beaker containing the two powders is heated at 80° C. The paraffin is fully melted and stirred evenly to achieve uniform mixing of the TiC nanosheets in the paraffin.

[0108] (3) The heated paraffin wax and TiC nanosheet mixture is cooled and granulated to obtain a paraffin wax and TiC nanosheet mixed powder, which is added into a specific annular mold. The dry pressing pressure is 2 MPa, the holding time is 60 s, and an annular test sample is obtained. The electromagnetic parameters of the test sample are tested at 2 to 18 GHz.

[0109] (4) Use a vector network analyzer (E5071C) to test the electromagnetic parameters of the prepared ring sample. The test environment is normal temperature and pressure. The obtained electromagnetic parameters are converted according to the public information to obtain the electromagnetic wave absorption performance of the test sample in the 2-18 GHz band, such as Figure 5 shown.

[0110] from Figure 5 It can be seen that when the TiC nanosheet loading is 35%, the effective absorption bandwidth of the composite material in the frequency range of 2 to 18 GHz is 3.52 GHz, the best matching thickness is 1.6 mm, and the minimum reflection loss is -14.77 dB, which proves that the composite material has good electromagnetic wave absorption performance at this matching thickness.

[0111] Application Example 2 :This application example tests the electromagnetic wave absorption performance of the titanium carbide nanosheets prepared in Example 1

[0112] (1) TiC nanosheets and paraffin were weighed according to a TiC nanosheet loading of 40%. The mass of the TiC nanosheets was 0.0533 g, and the mass of the paraffin was 0.08 g. They were added into a 5 mL beaker respectively.

[0113] (2) The small beaker containing the two powders is heated at 80° C. The paraffin is fully melted and stirred evenly to achieve uniform mixing of the TiC nanosheets in the paraffin.

[0114] (3) The heated paraffin wax and TiC nanosheet mixture is cooled and granulated to obtain a paraffin wax and TiC nanosheet mixed powder, which is added into a specific annular mold. The dry pressing pressure is 2 MPa, the holding time is 60 s, and an annular test sample is obtained. The electromagnetic parameters of the test sample are tested at 2 to 18 GHz.

[0115] (4) Use a vector network analyzer (E5071C) to test the electromagnetic parameters of the prepared ring sample. The test environment is normal temperature and pressure. The obtained electromagnetic parameters are converted according to the public information to obtain the electromagnetic wave absorption performance of the test sample in the 2-18 GHz band, such as Figure 6 shown.

[0116] from Figure 6It can be seen that when the TiC nanosheet loading is 40%, the effective absorption bandwidth of the composite material in the frequency range of 2 to 18 GHz is 3.12 GHz, the best matching thickness is 1.6 mm, and the minimum reflection loss is -26.93 dB, which proves that the composite material has good electromagnetic wave absorption performance at this matching thickness.

[0117] Application Example 3 :This application example tests the electromagnetic wave absorption performance of the titanium carbide nanosheets prepared in Example 1

[0118] (1) TiC nanosheets and paraffin were weighed according to a TiC nanosheet loading of 45%. The mass of the TiC nanosheets was 0.0533 g, and the mass of the paraffin was 0.08 g. They were added into a 5 mL beaker respectively.

[0119] (2) The small beaker containing the two powders is heated at 80° C. The paraffin is fully melted and stirred evenly to achieve uniform mixing of the TiC nanosheets in the paraffin.

[0120] (3) The heated paraffin wax and TiC nanosheet mixture is cooled and granulated to obtain a paraffin wax and TiC nanosheet mixed powder, which is added into a specific annular mold. The dry pressing pressure is 2 MPa, the holding time is 60 s, and an annular test sample is obtained. The electromagnetic parameters of the test sample are tested at 2 to 18 GHz.

[0121] (4) Use a vector network analyzer (E5071C) to test the electromagnetic parameters of the prepared ring sample. The test environment is normal temperature and pressure. The obtained electromagnetic parameters are converted according to the public information to obtain the electromagnetic wave absorption performance of the test sample in the 2-18 GHz band, such as Figure 7 shown.

[0122] from Figure 7 It can be seen that when the TiC nanosheet loading is 45%, the effective absorption bandwidth of the composite material in the frequency range of 2 to 18 GHz is 3.44 GHz, the best matching thickness is only 1.0 mm, and the minimum reflection loss is -19.61 dB, which proves that the composite material has good electromagnetic wave absorption performance at this matching thickness.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing cubic TiC nanosheets, characterized in that: The specific steps are: add Ti3C2T x , ammonia and formaldehyde, and condensation reaction was carried out to obtain carbon-coated Ti3C2T x , the carbon-coated Ti3C2T x The cubic TiC nanosheets are obtained by calcining.

2. The method for preparing cubic TiC nanosheets according to claim 1, characterized in that: The Ti3C2T x is achieved by adding multilayer Ti3C2T x The mixed solution is added to the raw material powder to obtain a few-layer Ti3C2T x ; Wherein, the mixed solution includes 25% tetramethylammonium hydroxide solution and water; the volume ratio of the 25% tetramethylammonium hydroxide solution to water is 4:1; Preferably, the multilayer Ti3C2T x The mass volume ratio of powder to mixed solution is 0.1-0.4 g:50 mL.

3. The method for preparing cubic TiC nanosheets according to claim 1, characterized in that: The intercalation thinning process is to multilayer Ti3C2T x The solution obtained by mixing the powder and the mixed solution is first subjected to ultrasonic treatment for 0.5 to 2 hours, and then subjected to magnetic stirring operation; preferably, the speed of the magnetic stirring is 1000 to 1200 r / min, and the stirring time is 24 to 48 hours; After the intercalation thinning process is completed, the intermediate needs to be filtered and washed with deionized water and ethanol in turn, and then dried for 20 to 30 minutes to obtain a few-layer Ti3C2T x .

4. The method for preparing cubic TiC nanosheets according to claim 1, characterized in that: The mass volume ratio of 3-aminophenol to deionized water in the aqueous solution of 3-aminophenol is 0.1-0.3 g:30 mL; Preferably, the aqueous solution of 3-aminophenol, the Ti3C2T x , the volume ratio of ammonia water and formaldehyde is 300:300:1~5:1~3.

5. The method for preparing cubic TiC nanosheets according to claim 1, characterized in that: The solution after the condensation reaction needs to be centrifuged and dried in sequence; Wherein, the centrifugal speed is 4600-4800 r / min, and the single centrifugal time is 7-10 min; The centrifugation is firstly performed by centrifugation washing with deionized water for 2 to 3 times, and then by centrifugation washing with anhydrous ethanol for 1 to 2 times; the powder after the centrifugation is placed in an oven for drying at a drying temperature of 60° C. for a drying time of 2 to 4 hours.

6. The method for preparing cubic TiC nanosheets according to claim 1, characterized in that: The calcination reaction is carried out in an inert atmosphere, wherein the inert atmosphere is one or a combination of hydrogen, nitrogen and argon; Wherein, the flow rate of the inert atmosphere is 80 to 120 sccm; preferably, the flow rate of the inert atmosphere is 100 sccm; Preferably, the calcination reaction is carried out by heating to 1200-1400° C. at a heating rate of 1-5° C. / min and keeping the temperature for 1-4 hours.

7. A cubic phase TiC nanosheet, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the cubic TiC nanosheets prepared by the preparation method according to any one of claims 1 to 6 and / or the cubic TiC nanosheets according to claim 7 in the field of electromagnetic wave absorption.

9. A method for testing the electromagnetic wave absorption performance of cubic TiC nanosheets, characterized in that: The cubic TiC nanosheets according to claim 8 are uniformly mixed with paraffin wax, and the mixture is post-treated to test the electromagnetic wave absorption performance of the cubic TiC nanosheets; Preferably, the uniform mixing of the cubic phase TiC nanosheets and paraffin wax refers to weighing TiC nanosheets and paraffin wax according to a certain loading amount of TiC nanosheets, melting the paraffin wax by heating, and stirring, thereby achieving uniform mixing of the TiC nanosheets in the paraffin wax; Wherein, the loading amount of the TiC nanosheets is 20% to 60%; the total mass of the TiC nanosheets and paraffin is controlled at 0.1g to 0.2g; preferably, the loading amount of the TiC nanosheets is 35%, 40%, or 45%; Preferably, the temperature of the heating treatment is 70-90°C.

10. The testing method according to claim 9, characterized in that: The post-treatment refers to cooling and granulating the paraffin wax and TiC nanosheet mixture after the heating treatment to obtain a paraffin wax and TiC nanosheet mixed powder, adding the mixed powder into a mold, and dry pressing to obtain a test sample; Preferably, the dry pressing pressure is 1-10 MPa, and the holding time is 30s-120s; Preferably, the test sample is prepared by performing electromagnetic parameter testing on the sample using a vector network analyzer, the test environment is normal temperature and pressure, and the obtained electromagnetic parameters are converted through a formula to obtain the electromagnetic wave absorption performance of the test sample in the 2 to 18 GHz band.